2003
DOI: 10.1103/physrevlett.90.237201
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-Dissipation Ratio of the Heisenberg Spin Glass

Abstract: Fluctuation-dissipation (FD) relation of the three-dimensional Heisenberg spin glass with weak random anisotropy is studied by off-equilibrium Monte Carlo simulation. Numerically determined FD ratio exhibits a "one-step-like" behavior, the effective temperature of the spin-glass state being about twice the spin-glass transition temperature, T eff ≃ 2Tg, irrespective of the bath temperature. The results are discussed in conjunction with the recent experiment by Hérisson and Ocio, and with the chirality scenario… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 22 publications
8
53
1
Order By: Relevance
“…Following up [16] the present data confirm that there is a major contribution to the AHE linked to the presence of chirality which persists up to T ∼ 150K and which can be interpreted satisfactorily in terms of the chiral AB-related mechanism [11,12,13].…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Following up [16] the present data confirm that there is a major contribution to the AHE linked to the presence of chirality which persists up to T ∼ 150K and which can be interpreted satisfactorily in terms of the chiral AB-related mechanism [11,12,13].…”
Section: Introductionsupporting
confidence: 69%
“…At low temperatures, this term is large enough to dominate the KL term over almost the entire re-entrant region. Because of the clear correlation with the presence of canting, the difference term can be confidently identified with the theoretically predicted chiral or real space Berry phase term [11,12]. It can be noted that in the presence of the chiral AHE the standard Equation (1) can still be written down formally, but it loses all transparency because physical phenomena depending not only on the bulk magnetization but on the details of the transverse local spin structure and its dynamics will be hidden within the AHE parameter R s (T ).…”
Section: Hall Measurements and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Our system has a strong heisenberg character, 28 and it has been shown that in such case, the spin glass transition should correspond to chiral ordering with one-step RSB. 28,29 Numerical simulations on an heisenberg system with weak anisotropy have been performed recently, 30 whose results are characteristic of one RSB, with T ef f higher than but independent of the bath temperature: in other words, a "universal" -constant T ef f -χ(C) curve is obtained. In a one-RSB system, it can be shown that ∆ and q EA are related simply by q EA = 1/(1 + γT /T ef f ) where γ = (1 − ∆)/∆.…”
Section: Discussion: the Fluctuation Dissipation Graphmentioning
confidence: 99%